2019
DOI: 10.1371/journal.pbio.3000364
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal delta-6-desaturase activity determines host range for Toxoplasma sexual reproduction

Abstract: Many eukaryotic microbes have complex life cycles that include both sexual and asexual phases with strict species specificity. Whereas the asexual cycle of the protistan parasite Toxoplasma gondii can occur in any warm-blooded mammal, the sexual cycle is restricted to the feline intestine. The molecular determinants that identify cats as the definitive host for T. gondii are unknown. Here, we defined the mechanism of species specificity for T. gondii sexual development and break the species barrier to allow th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 34 publications
(48 reference statements)
1
108
0
2
Order By: Relevance
“…This is also seen in mature female gametes; however it appears to be missing from the male gamete [52,53]. Recently it was shown that increasing the availability of linoleic acid, through supplementation and inhibition of downstream metabolism, allows the generation of T. gondii sexual stages in mice [54]. This may allow the study of these elusive sexual stages, opening the possibility of examining T. gondii metamorphosis for the first time.…”
Section: Demolition and Developmentmentioning
confidence: 99%
“…This is also seen in mature female gametes; however it appears to be missing from the male gamete [52,53]. Recently it was shown that increasing the availability of linoleic acid, through supplementation and inhibition of downstream metabolism, allows the generation of T. gondii sexual stages in mice [54]. This may allow the study of these elusive sexual stages, opening the possibility of examining T. gondii metamorphosis for the first time.…”
Section: Demolition and Developmentmentioning
confidence: 99%
“…2 and Table 1). Organoid derivation from other domesticated and laboratory animals, including pigs, dogs, cats and rats, have also been described 24,[37][38][39] , and a similar culture setting further allowed an organoid expansion of snake venom glands 40 , underscoring the cross-species versatility of the organoid culture system. It should be noted that the growth factor combinations are not only tailored to individual tissues but also include unique molecules in some cases, such as gastrin for digestive tissues, neuregulin-1 for mammary organoids 7,18,19 , dihydrotestosterone for prostate organoidsd 6,41 and forskolin for human liver bile duct organoids 25 but not for hepatocyte organoids 26 .…”
Section: Somatic Cell-derived Organoids As Prototypes Of Human Epithementioning
confidence: 92%
“…Toxoplasma gondii is one of the most common parasites in the human population and has two main lifecycle phases: the sexual stage that is restricted to the cat intestinal epithelium and the asexual stage that can occur in any warm-blooded animals. A study using feline small intestinal organoids as a definitive host identified linoleic acid abundance or a deficiency of delta-6-desturase, an enzyme that is essential for linoleic acid metabolism, as a determinant of sexual reproduction of T. gondii 39 , and another study infected bovine and porcine small intestinal organoids with T. gondii tachyzoites as a model of invasion to intermediate hosts 38 .…”
Section: Organoid Reverse Engineering For Genetic Disease Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the characterized PLP containing genes have shown activity in vitro, which could again indicate a need for additional host factors and further optimized assay buffers for parasite PLPs. Lipid metabolism and signaling is critical during the parasite lifecycle [36], but there is still much to discover about these complex processes. Future work on the remaining T. gondii PLPs and other parasite derived PLPs may reveal novel regulators of parasite replication, infection and virulence.…”
Section: Plos Pathogensmentioning
confidence: 99%